The Value of Choices: The DIAL Project - Tartaglia, Raffaella (Mimesis Journal, 2024)
Adopting a sociological perspective, this article focuses on the value of the artwork and its conservation, specifically delving into issues related to the relationship between art and society. The discussion starts from the complex system of value attribution to distinguish, on the one hand, the human factors involved from the moment of the work's creation until its fruition and, on the other hand, how to manage them through new conservation methods that can support museum strategies suitable for the management of complex works. To that end, the DIAL (Digital Index of an Artwork's Life) is proposed as a case study.